Background concentrations of metals in regolith near J. G. Mendel Czech Antarctic Station - Uher, A.; Coufalík, P. (Pavel); Zvěřina, O.; Ticová, B.; Novotný, K.; Komárek, J. (2016)
The anthropogenic activities, especially construction and operation of polar stations, should be harmless to the environment. This work focuses on determination of metals in regolith in the vicinity of the Johann Gregor Mendel Czech Antarctic Station (S 63°48'02'', W 57°52'57'') on James Ross Island. The regolith in this location was not polluted by metals during building of the station and its operation.